PWE-064 Routine post-operative contrast swallows following anti-reflux surgery and hiatus hernia repair: selective use is preferred. (28th May 2012) - Alkhaffaf, B; Turner, P; Date, R; Mughal, M; Ward, J; Pursnani, K
Abstract : Introduction: The routine use of post-operative contrast studies following gastric fundoplication surgery is contentious. This study aimed to determine whether routine contrast studies were more likely to identify significant post-operative complications when compared to their selective use. Methods: This was a retrospective study of 241 consecutive patients undergoing primary gastric fundoplication. The primary outcome measure was the identification of significant complications (intrathoracic migration, perforation, volvulus or obstruction) by water-soluble contrast swallow that warranted further intervention or immediate reoperation. Results: Routine contrast studies (Group A) performed in 125 patients identified 6 abnormalities. Of the remaining 116 patients (Group B), 11 underwent selective contrast studies of which one was abnormal. Two patients from Group A underwent immediate reoperation as a result of the contrast study compared to none from group B (p=1.000). One patient from Group A presented 3 days following discharge with an incarcerated hiatus hernia requiring reoperation despite a normal post-operative contrast study. The incidence of radiologically detected abnormalities was greater in patients whose primary indication for surgery was large hiatus hernia compared to those whose surgery was primarily for gastro-oesophageal reflux; however this was not statistically significant (11% vs 2% respectively; p=0.051). Conclusion: The routine use of contrast studies following gastric fundoplication is unnecessary as it does not identify a greater number of significant acute post-operative complications when compared to the selective use of such investigations. Competing interests: None declared.